2013
DOI: 10.2166/wst.2013.179
|View full text |Cite
|
Sign up to set email alerts
|

In vivo endocrine disruption assessment of wastewater treatment plant effluents with small organisms

Abstract: Surface water receives a variety of micro-pollutants that could alter aquatic organisms' reproduction and development. It is known that a few nanograms per litre of these compounds can induce endocrine-disrupting effects in aquatic species. Many compounds are released daily in wastewater, and identifying the compounds responsible for inducing such disruption is difficult. Methods using biological analysis are therefore an alternative to chemical analysis, as the endocrine disruption potential of the stream as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Using oligo microarray and qPCR analyses, they found that WWE and T 3 exposures significantly increased the expression of TH-sensitive genes: thrb, dio2, crhbp , and fap (Table 4). The in vivo effects of WWE on TH-linked gene expression was also demonstrated by Castillo et al in a transgenic X. laevis harboring a thibz -GFP reporter construct that was activated by WWE exposure (Table 4) (188).…”
Section: Complex Mixturessupporting
confidence: 54%
“…Using oligo microarray and qPCR analyses, they found that WWE and T 3 exposures significantly increased the expression of TH-sensitive genes: thrb, dio2, crhbp , and fap (Table 4). The in vivo effects of WWE on TH-linked gene expression was also demonstrated by Castillo et al in a transgenic X. laevis harboring a thibz -GFP reporter construct that was activated by WWE exposure (Table 4) (188).…”
Section: Complex Mixturessupporting
confidence: 54%
“…Thyroid hormone signaling is essential for metabolism, growth, and organ development, including the brain. , While some studies reported thyroid receptor α (TRα)­activation by (un)­treated wastewater, , only four studies (5 assays) included advanced wastewater treatment technologies and detected no thyroid activity in the effluents of the CT or the advanced treatment. ,,, In contrast, in vivo studies with the Xenopus embryonic thyroid assay (XETA) suggest the occurrence of thyroid disruptors in conventionally treated wastewater, which is not surprising, given that these compounds often act via non-receptor-mediated mechanisms . Thus, the XETA assay or in vitro bioassays for thyroid hormone biosynthesis (e.g., inhibition of the sodium-iodide symporter) are more relevant than TRα activation to investigate the removal of thyroid disruptors by (advanced) wastewater treatment.…”
Section: Removal Of In Vitro Toxicitymentioning
confidence: 99%
“…At the organismal level, the thyroid system represents an important target of endocrine disruption (Boas, Feldt-Rasmussen, & Main, 2012;Brucker-Davis, 1998), thereby prompting development of the Xenopus metamorphosis assay for screening TH-disrupting chemicals (Opitz et al, 2005). A high-throughput, whole-tadpole method using transgenic animals that express green fluorescent protein upon exposure to TH-disrupting chemicals was also developed (Castillo et al, 2013;Fini et al, 2007). At the receptor level, the two TR isoforms, a and b, have distinct tissue-specific expression patterns (Cheng et al, 2010), such that use of TR antagonists and TR isoform-selective agonists may enable targeting specific tissues and avoid affecting off-target tissue-specific side-effects.…”
Section: Tool For Screening Th-active Compoundsmentioning
confidence: 99%